An individualized telephone-based care support program for rural family caregivers of people with dementia: study protocol for a cluster randomized controlled trial - Yao Wang (BMC, 2021)
Abstract Background There are about 9.5 million people with dementia in China. Up to 99% of them are cared for by their family caregivers. Family caregivers are confronted with considerable difficulties and challenges while providing care. They often experience high levels of emotional, physical, financial, and social burdens. Caregivers in rural areas experience an even higher level of burden compared to their counterparts in urban areas due to fewer health resources for dementia care. However, so far, no intervention study has been conducted to support family caregivers in rural areas of China. The aim of this proposed study is to adapt and evaluate an evidence-based and culturally-tailored individualized telephone-based care support (ITBCS) program for family caregivers of people with dementia in rural China. Methods A cluster randomized controlled trial (RCT) will be conducted to evaluate the effectiveness of the ITBCS compared with usual care for Chinese rural family caregivers of people with dementia. A total sample of 168 rural family caregivers will be recruited. The intervention components consist of a 3-month intensive telephone-based care support intervention followed by telephone-based follow-up consultations for 6 months. The control group will receive usual care services available for them. Outcome measures include carers’ subjective burden, depressive symptoms, health-related quality of life, social support, caregiving self-efficacy, and care recipients’ difficult behaviours and competence in activities of daily living at 3, 9 and 15 months after baseline. The potential cost-effectiveness of the ITBCS compared with usual care will be assessed as well. Discussion If effective, the ITBCS program can be adapted and used in rural areas of China as a blueprint to improve the quality of home-based care for people with dementia. Findings from the present study are significant for developing evidence-based dementia care policy in rural China. Trial registration Chinese Clinical Trial Registry, ChiCTR2000038821 , Registered 4 April 2020, http://www.chictr.org.cn/showprojen.aspx?proj=62268 .